Lung function benefits of traditional Chinese medicine Qiju granules against fine particulate air pollution exposure: a randomized controlled trial - Chen, Rucheng; Zhang, Lu; Gu, Weijia; Li, Ran; Hong, Huihua; Zhou, Linshui; Zhang, Jinna; Wang, Yixuan; Ni, Ping; Xu, Shuqin; Wang, Zhen; Sun, Qinghua; et al. (Frontiers in Medicine, 2024)
Introduction: Multiple targets are considered as the causes that ambient fine particulate (aerodynamic diameters <2.5 μm [PM2.5]) induced lung function injury. The Qiju granules are derived from the traditional Chinese medicine (TCM) formula, Qi-Ju-Di-Huang-Wan (Lycium, Chrysanthemum, and Rehmannia Formula, QJDHW), which has been traditionally used to treat symptoms such cough with phlegm, dry mouth and throat, and liver heat. This treatment approach involves attenuating inflammation, oxidative stress and fibrosis response. This study investigated the effects of Qiju granules on protecting lung function against PM2.5 exposure in a clinical trial.Methods: A randomized, double-blinded, and placebo-controlled trial was performed among 47 healthy college students in Hangzhou, Zhejiang Province in China. The participants were randomly assigned to Qiju granules or control group according to gender. Clinical follow-ups were conducted once every 2 weeks during a total of four-week intervention. Real-time PM2.5 concentrations to which participant was personally exposed was monitored. Data on individual characteristics, heart rate (HR), blood pressure (BP), lung function at baseline and during the follow-ups were collected. The effects of PM2.5 exposure on lung function were assessed within each group using linear mixed-effect models.Results: Forty eligible participants completed the scheduled follow-ups. The average PM2.5 level was 64.72 μg/m 3 during the study period. Significant negative correlation of lung function with PM2.5 exposure concentrations was observed, and 1-week lag effect was observed. FEV1, PEF, MMEF, FEF75, FEF50 and FEF25 were significantly decreased by PM2.5 exposure in the control group. Small airway function was impaired more seriously than large airway function when PM2.5 exposure concentrations was increased. In the Qiju granules group, the associations between lung function and PM2.5 exposure become much weaker and no statistical significance. Conclusions: PM2.5 exposure was associated with reduced lung function. TCM Qiju granules may be an effective in protecting lung from the adverse effects of PM2.5 exposure.